Analisis Resepsi Penonton Atas Popularitas Instan Video Youtube Keong Racun Sinta dan Jojoe - Suryani, Any (Universitas Semarang, 2013)
Keong Racun Sinta dan Jojo YouTube Video is the beggining of instant popularity phenomena. Video maker s popularity is the result of viewers reception by watching their lipsync style singing a song titled Keong Racun .Reception analysis conducted by semiotic analysis based on Triangle Meaning Theory by Pierce consisting of sign, object, and interpretant of the video.The result of the semiotic analysis is the meaning as preferred reading which show narcissism expression of the video maker to attrack viewers attention. Further, the research did indepth interview with four informants who randomly selected based on specific criterias (purposive sampling) to get their reception. The data of interview categorized and compared with preferred reading of the video so there are three positions of reception analysis : dominant-hegemonic reading, negotiated reading, and oppositional-hegemonic reading.